COVID‐19's impact on Australian wine markets and regions. (9th August 2021) - Wittwer, Glyn; Anderson, Kym
Abstract : This paper provides an empirical case study of impacts of COVID‐19 on Australia's wine sector. Wine exports were subject to disruptions and, like domestic wine sales, were adversely affected not only by temporary declines in consumers' expected incomes but also by the social distancing measures and self‐isolation that led to closure of restaurants, bars, cafes and clubs plus declines in international travel and tourism. Partly offsetting this has been a boost to off‐premise and direct e‐commerce sales. We first estimate those impacts and their expected partial recovery in 2021 using a new model of global beverage markets. Then, we add results on regional effects, including through domestic wine tourism, using a new economy‐wide model with sub‐national regions. The paper concludes by drawing lessons on how this sector's resilience to future global shocks could be strengthened.